2014
DOI: 10.1002/app.41297
|View full text |Cite
|
Sign up to set email alerts
|

An innovative material based on natural rubber and leather tannery waste to be applied as antistatic flooring

Abstract: In recent decades, the production chain of beef and bovine leather has grown significantly because of an increase in the world's population and improved access to consumption. However, the generation of waste derived from this sector has grown simultaneously, and consequently, improved ways of adding value, reusing, and disposing these waste materials are being sought. In this article, we present a new and innovative composite material based on vulcanized natural rubber (NR), carbon black (CB), and leather was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
0
13
0
7
Order By: Relevance
“…This is due to the agglomeration of WLB fibers at higher loading (above 20%) which increased the defects in composites. Zhang et al observed a decrease in EB value for PLA natural fiber composites with increase in natural fiber content . They attributed it to the nucleating ability of natural fiber which increases the crystallization of PCL which in turn decrease the EB value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the agglomeration of WLB fibers at higher loading (above 20%) which increased the defects in composites. Zhang et al observed a decrease in EB value for PLA natural fiber composites with increase in natural fiber content . They attributed it to the nucleating ability of natural fiber which increases the crystallization of PCL which in turn decrease the EB value.…”
Section: Resultsmentioning
confidence: 99%
“…Composites based on leather wastes as fillers are reported to be useful for many applications such as in construction materials, automobile interior moldings, heat and sound insulating boards, shoe soles, flooring materials, and moldings with good anti‐static properties, air permeability and good appearances . Ruiz et al developed material based on natural rubber and leather tannery waste to be applied as antistatic flooring. However, utilization of waste leather as filler in biodegradable polymer based composites has not been reported till now.…”
Section: Introductionmentioning
confidence: 99%
“…La preparación de los compuestos fue llevado a cabo en un molino abierto de acuerdo a la norma ASTM D 3182 [58], El sistema de vulcanización consistió de óxido de zinc (5 phr), ácido esteárico (3 phr), azufre (2.5 phr) y ZMB-2 (1 phr), y un sistema de aceleración que consistió en MBTS (1.2 phr) y TMTD (0.4 phr). Los tiempos de vulcanización de los compuestos fueron obtenidos antes del moldeo por compresión mediante ensayos reométricos [59].…”
Section: Mezclas De Caucho Con Residuos De Cuero Posindustrialunclassified
“…Los materiales antes y después de la exposición a los diferentes agentes químicos fueron caracterizados mediante FTIR, SEM-EDX, medidas eléctricas de corriente directa y alterna, dureza, resistencia a la tracción, a la compresión y a la abrasión [59]. A partir de los resultados de las micrografías SEM y las difracciones de rayos X, se puede concluir la presencia de metales como Na, Al, Si, k, Ca, Fe y Zn, adicionalmente fue encontrado un pico de cromo y este fue relacionado a la base CrOHSO4 utilizada en el proceso de teñido del cuero.…”
Section: Mezclas De Caucho Con Residuos De Cuero Posindustrialunclassified
See 1 more Smart Citation